Enriching Students’ Vocabulary through Reading Short Story Case Study of the 1st Year Student at Faculty of Education, Souphanouvong University : https://doi.org/10.69692/SUJMRD0802109 - SIDAVONG, Khanthaly; PANMANIVONG, Thavone; LAMPHAIPHANH, Ketsalin; SOULIYA, Toulakone; PHANFONGPHET, Sipaseuth (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purpose of this research was to investigate (1) the enrichment of students’ English vocabulary through reading short story technique of the first-year students at Department of Language Pedagogy, Faculty of Education, Souphanouvong University, Luangprabang Province, Laos, in academic year 2019-2020, and (2) the students’ reaction toward the use of short stories in enriching their English vocabulary. The participants of this study were the first-year students with the total number of 28 students. Pre-test and post-test and observation were employed to be the instruments of this study. The mean score, percentages and T-values for both pre-test and post-test were calculated through the SPSS program. The result of data analysis was clearly shown with the mean score of the pre-test was 17.03 and S.D was 4.59 while the mean score of the post-test was 22.42 and S.D was 4.20. Based on the result of the data analysis, the mean sore of the post-test was greater than the mean score of pre-tests. Also, the observation results showed that students enjoyed and engaged in the reading activities provided while and after using this technique. This can be concluded that the use of short stories is one of the effective techniques that would be useful in classes, and is also be able to engage learners to learn English - vocabulary with an interesting and effective way in Learning English.